18F-Fluoromisonidazole PET in Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disease Presenting With Tumefactive Demyelinating Lesion. (May 2021) - Mitamura, Katsuya; Norikane, Takashi; Takata, Tadayuki; Yamamoto, Yuka; Nishiyama, Yoshihiro
Abstract : Abstract: Tumefactive demyelinating lesions have been appreciated as part of the clinical and radiological spectrum of myelin oligodendrocyte glycoprotein antibody–associated disease. A 63-year-old woman was followed up for myelin oligodendrocyte glycoprotein antibody–associated disease. Two years later, she presented with right facial paralysis. T2-weighted MRI scan demonstrated a high-signal-intensity area with edematous change in the right frontal lobe, and partial enhancement was shown on contrast-enhanced T1-weighted image. This contrast-enhanced area showed increased 18 F-fluoromisonidazole uptake.